Perlindungan Hukum Asuransi Pengguna Jalan Tol Oleh PT. Jasa Raharja Saat Mengalami Kecelakaan Lalu Lintas Pada Ruas Jalan Tol Jakarta-Cikampek - Edelweiss Ratna Fauziah; Yetti Royati; Imanudin Affandi (Wajah Hukum, 2021)
Insurance comes from the word vezekering which means coverage. The person who is covered is called vezekerde and the insurance company is called verzekeraar. Initially, insurance has to manage, transfer or share risks, along with economic development and development developments in various sectors in the fields of industry, economy, infrastructure and technology, causing more problems to occur, especially problems regarding legal protection for the community, along with developments in the field of infrastructure development, for example in toll road construction, so that legal protection for toll road users is urgently needed. Social insurance is social insurance established by the Indonesian government based on statutory regulations, when viewed from the social insurance legal products that have been issued in Indonesia, it can be seen that social insurance programs are generally known, one of which is the Passenger Accident Social Insurance which is currently better known as Jasa Raharja. And to carry out coverage, the Indonesian government appointed PT Asuransi Jasa Raharja to manage and distribute compensation funds to traffic accident victims including traffic accident victims on the Jakarta-Cikampek toll road.